Integration of PAI Learning Methods Based on Sorogan and Discovery Learning at Khadijah Senior High School Surabaya - Ahmad Wildan Saifullah, Alaina; Uroidli, Ali; Ayu Cahya Ningrum, Annisa Eka; Fahmi, Yusril Fahmi; Fuad, Ah. Zakki (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
PAI teachers' efforts to develop learning both outside and inside the classroom are very varied, especially in maximizing digital media to support increased students' understanding. The urgency of using digital in learning is something that every teacher naturally has, because the teacher's ability to use digital in learning can help the learning methods used by teachers become more varied and not monotonous. Especially at Khadijah High School which has really maximized media in its learning, of course the sorogan and discovery learning methods that are applied will not be able to work if it is not accompanied by the teacher's ability to utilize media for learning, in addition to the teacher's ability to master devices, media and the use of learning methods, Teachers must also have content and materials, so that they all support the learning process and increase understanding not only of students' cognitive, but also affective improvement. In this research, we will examine further the integration of sorogan and discovery learning methods at SMA Khadijah Surabaya.